Isotopic and geothermobarometric characterisation of metasedimentary rocks from the central Araçuaí-Ribeira orogenic system and its eastern basement: geotectonic implications - Reik Degler (2017)
The Araçuaí-Ribeira orogenic system (AROS) located in south eastern Brazil comprises a wealth of lithologies, which reflect the geotectonic evolution of the region since the Precambrian. Demonstrably two large-scale orogenic events had a lasting influence on the regional geology and allow certain correlations withinthe AROS and with further stratiform rock units in SE Brazil and Africa. The extensive magmatic arc activity during the Rhyacian-Orosirian orogenic event originated the basement of this orogenic system (ROOS) and can be subdivided in relation to its evolution in a continental or oceanic magmatic arc setting. Remnants of the juvenile arc setting are the ortho-derived Juiz de Fora and Pocrane complexes. They comprise rock units representing the juvenile AROS basement. U-Pb ages of Juiz de Fora and Pocrane complexes samples point out an age interval of c. 2250 to c. 1800 Ma and show best concordance between 2184 ± 9 and 2080 ± 19 Ma for the protoliths crystallisation. The Hf in zircon data disclose juvenile to moderately juvenile signatures for both the Pocrane and Juiz de Fora complexes, which form a quite primitive magmatic arc similar to a modern intra-oceanic island arc system.(Hf TDM c. 2.2 Ga) between 2196 and 1864 Ma (Hf(t) +8.2 to -3.5). Our data together with a thorough compilation from the literature allows us to envisage a complex system of orogens developed in Rhyacian-Orosirian time (ROOS). This system would include: a Western-ROOS, and Juvenile-ROOS and an Eastern-ROOS. Large parts of the AROS are covered by metasedimentary rocks. Detrital zircons from samples of the western AROS contain grains of 2158-830 Ma (Hf(t) from -2.2 to -22.7) and suggest sediment sources located in the Rhyacian basement to the Tonian rift magmatism. Samples from the southwestern AROS have a more complex assemblage of detrital grains (987-592 Ma, Hf(t) from +14.9 to -2.9) and indicate provenance from mainly juvenile sources of distinct ages. Samples from the eastern section dated between 650-552 Ma show negative Hf(t) (-25.3 to -16.5) and suggest main sediment sources in the Rio Doce arc formed in the Brasiliano orogeny. A retrograde metamorphic path in high amphibolite facies between 621-480 Ma is typical of collisional orogens and also records a late thermal event. The studied paragneisses represent distinct Neoproterozoic basin stages, shifting from passive to active margin settings. Further, the detrital and metamorphic chronometers imply constrains in relation to the West Gondwana assembly in the final stages of the AROS geotectonic evolution.